Deoxycholate-Treated, Nontoxic, Whole-Cell Vaccine Protective Against Experimental Salmonellosis of Mice - Badakhsh, Fred F. (1969)
A vaccine prepared from the residue after extraction of whole cells of Salmonella typhimurium with 2% sodium deoxycholate proved to be nontoxic and highly immunogenic. The material was not lethal for mice at 6.0 mg and was essentially nontoxic in rabbit skin, whereas endotoxic activity was found in the dialyzed extract. A high dosage, above 2.0 mg, was less protective than lower doses, indicating a degree of “immunologic paralysis.” Three inoculations of low doses, 0.25 mg each, induced protection against death and tissue infection in animals challenged with 2,000 ld(50) of virulent homologous S. typhimurium and against death, but not against tissue infection, after heterologous challenge with S. enteritidis. Residues of purified cell walls were as effective as residues of whole cells, indicating that the immunizing antigen(s) resided in the cell wall.